A model for an urban structure on the Cape Flats - Fox, Revel, 1924- (School of Architecture, Planning and Geomatics, 2024)
In 1966 the American Institute of Planners mounted a two year consultation to study the Next Fifty Years. Part 1 was entitled Optimum Environment with Man as the Measure. It was this arresting theme and the papers that flowed from it ( 1) that became the central idea and the broad objective of the study. The method by which this study is carried out is by means of a model for an urban structure, as a basis for a satisfactory framework for human settlement. After due consideration a purely abstract diagram is rejected in favour of a model designed in conformity with all known criteria but theoretical in the sense that detailed topographical and locality constraints are subdued. With this method the essential nature of the diagram is undiluted, and the processes of analysis are easily grasped.